Health Professionals and Pharmacists Awareness and Attitude Towards Counterfeit Medicine - Chaudhary, Sabina (Journal of Nepal Health Research Council, 2023)
Background: Counterfeit medicine is not only illegal, but it is also an insidious threat and poses serious public health and safety concern. Health professionals can play an important role in campaign against counterfeit drugs by staying vigilant, reporting suspicious products and preventing the distribution of counterfeit medicine. The present study aims to assess the awareness and attitude towards counterfeit medicine among health professionals and pharmacists in Nepal. Methods: It was a cross-sectional study conducted among 264 health professionals and pharmacists of Saptari, Nepal. Samples were recruited by quota sampling technique and pretested, self-administered questionnaire were used for collecting data regarding socio-demographic, knowledge and attitude on counterfeit medicine. Descriptive & inferential statistics were used to analyze the data generated. Results: This study found that mean knowledge score of respondent was 12.11±4.3 and only 31.7% (n=39) of the respondents had good knowledge on counterfeit medicine while 44.7% (n=55) showed moderate and 23.6% (n=29) had poor knowledge levels. Nurses, paramedics and pharmacists scored statistically lower than doctors, however there was no significant difference in knowledge between nurses and pharmacists (p<0.001). Mean attitude score was 3.82 (±0.68) and majority of respondents (85.3%) showed favorable attitude towards counterfeit medicine. Respondents having poor knowledge level had statistically significant unfavorable attitude towards counterfeit medicine Conclusions: The study highlighted the need for counterfeit medicine awareness campaigns and training to enhance the role of health professionals and pharmacists to recognize and report suspicious medicine and prevent counterfeit medicines-associated harms. Keywords: Attitude; counterfeit medicine; health professionals; knowledge; pharmacists